The Effect of Leadership Style, Motivation and Work Discipline on Employee Performance - Hamdi, Hamdi; Aqmarina, Nur; Kadir, Abdul; Naimah, Naimah (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The purpose of this study was to describe, analyze and find out the most dominant influence of competence, motivation, work discipline on the performance of the employees of the